Hubungan antara Oral Motor Skill dengan Kejelasan Bicara pada Anak dengan Down Syndrome di Surakarta - Fadhia Haya, Alfiana; Fitri, Anisyah Dewi Syah (Jurnal Terapi Wicara dan Bahasa, 2024)
Background: When speaking, children with Down Syndrome often say words that are unclear and difficult to understand, this occurs because there are problems with their Oral Motor skills. Objectives: To determine the relationship between Oral Motor Skill and speech intelligibility in children with Down Syndrome in Surakarta. Methods: This type of research is quantitative research with a correlational descriptive design and uses a cross-sectional data collection time approach. In taking samples using a cluster sampling technique as many as 30 children. Results: Based on the results of bivariate analysis tested using SPSS Spearman Rank, a significant value of 0.001 was obtained, where the results were smaller than 0.05, so it can be concluded that the alternative hypothesis (Ha) in this study was accepted, which means there is a significant correlation/relationship between Oral Motor Skills with speech clarity in children with Down Syndrome. The magnitude of the correlation/strength of the relationship is shown by the correlation coefficient (r) = 0.562, which means it has a positive correlation in the medium category. Conclusion: Based on the results of data analysis, it can be concluded that there is a relationship between Oral Motor Skill and speech intelligibility in children with Down Syndrome in Surakarta. Keywords: Oral Motor Skill, Speech Intelligibility, Down Syndrome